Electronic structure, optical and thermoelectric properties of CaMgSi1−xCx (x = 0, 0.5): an ab-initio study. (21st December 2018) - Khandy, Shakeel Ahmad; Khan, Wilayat; Islam, Ishtihadah; Laref, Amel; Tanveer, Muhammad; Gupta, Dinesh C; Rubab, Seemin; Laref, S
Abstract: In this study, the CaMgSi and its subsequent doping by carbon atoms has been systematically studied using the first-principles calculations. Ground state properties focusing particularly on the structural, optical and transport coefficients of these alloys are discussed. Semi-metallic character is prominent from the observed band profiles when GGA scheme is utilized. The enhancement of thermoelectric properties with a speculation from the electronic structure is observed when doped with carbon. Also, the thermoelectric properties are envisaged within the specific transport constraints in order to figure out the dimensionless figure of merit (zT). The Seebeck, electrical and thermal conductivity coefficients are calculated and thereby utilized to find out the extremum of zT for both these alloys. The maximum zT for CaMgSi is found to be 0.4 at 400 K and for CaMgSiC, its value increases to 0.8 at 800 K. Thus, the later compound can be developed as a high temperature thermoelectric material. The optical considerations of such alloys are predicted from the calculated values of optical conductivity, reflectivity and electron energy loss within the range of 30.00 eV of incident photons. Likewise, the active region of these alloys for possible application in optoelectronic devices is ultraviolet region because the ultraviolet frequencies are strongly absorbed by these compounds.